South Africa’s challenges pertaining to mine closure — the problem of abandoned and derelict mines in the Mpumalanga coalfields - van Tonder, DM; Coetzee, H (Mine Closure 2009: Proceedings of the Fourth International Conference on Mine Closure, 2009)
The long history of mining in South Africa has left a legacy of around six thousand abandoned mines scattered around the entire country. Many of these mines are situated in the Mpumalanga coalfields. Mining commenced at the turn of the previous century, initially with little environmental degradation associated with the mainly board and pillar mining method of the time. However, subsidence occurred due to pillars or strata floor collapsing, sometimes decades after mining ceased. Subsidence causes damage to surface infrastructure and interferes with the drainage of surface water and may also impact aquifers. Secondary effects included spontaneous combustion of abandoned coal mines being accelerated both above and below ground. Burning discard coal dumps present further potential for spontaneous combustion and air pollution from fugitive emissions of particulate matter and gases including methane (CH4), sulphur dioxide (SO2) and oxides of nitrogen (NOx). Acid water has been linked to the death of fish, crocodiles, frogs and cattle. Open cut coal mining also has the potential to irreversibly pollute the ‘pristine’ pans and lakes by disrupting their hydrology and ecology. This study focuses on the impacts and consequences of abandoned coal mines in the Mpumalanga coalfields and on prioritising them in terms of risks they pose to human health and the environment. The prioritisation of these mines for rehabilitation as a follow up on the strategy for the management of derelict and ownerless mines of South Africa is also discussed.